2016
DOI: 10.1093/aje/kwv296
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Environments and Incident Hypertension in the Multi-Ethnic Study of Atherosclerosis

Abstract: We examined relationships between neighborhood physical and social environments and incidence of hypertension in a cohort of 3,382 adults at 6 sites in the United States over 10 years of follow-up (2000-2011), using data from the Multi-Ethnic Study of Atherosclerosis. The sample was aged 45-84 years (mean = 59 years) and free of clinical cardiovascular disease and hypertension at baseline. Of the participants, 51% were female, 44% white, 23% Hispanic, 21% black, and 13% Chinese-American; 39% of participants de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 52 publications
(55 reference statements)
3
79
0
2
Order By: Relevance
“…[93] There were no significant associations between other neighborhood physical and social environment indicators and incident hypertension. These analyses used both survey-based and GIS measures of neighborhood environments and assessed the associations with cumulative average measures of these constructs.…”
Section: Select Findings To Datementioning
confidence: 99%
“…[93] There were no significant associations between other neighborhood physical and social environment indicators and incident hypertension. These analyses used both survey-based and GIS measures of neighborhood environments and assessed the associations with cumulative average measures of these constructs.…”
Section: Select Findings To Datementioning
confidence: 99%
“…more unhealthy foods on average and fewer opportunities for physical activity) and social environments (e.g. less safety and social cohesion) are associated with increased risk of CVD risk factors such as obesity, diabetes, and hypertension, and fatal and non-fatal CVD (Christine et al, 2015; Diez Roux et al, 2016; Kaiser et al, 2016; Kershaw et al, 2015). Studies have also documented that blacks and other racial/ethnic minorities disproportionately reside in neighborhoods that are socioeconomically disadvantaged, and have poor access to health promoting resources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the MESA neighborhood Study, an ancillary study to the Multi-Ethnic Study of Atherosclerosis (MESA), includes a set of novel time varying measures of healthy food availability and access to recreational facilities. Previous studies have shown that individuals living in neighborhoods with better food and physical activity environments are less likely to develop hypertension (Kaiser et al (2015)). In the present analysis, we are primarily interested in investigating whether a set of single nucleotide polymorphisms (SNPs) measured in a genome-wide association study modifies the effect of neighborhood exposures on longitudinal measures of blood pressure.…”
Section: Introductionmentioning
confidence: 99%